TEACHERS’ ROLES IN OVERCOMING SPECIAL NEEDS STUDENTS DIFFICULTIES IN LEARNING ENGLISH AT ELEMENTARY SCHOOLS IN BENGKULU CITY - Lidya Agustina; Kiagus Baluqiah; Dian Susyla; Eki Saputra (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The purpose of this study is to determine teachers roles in overcoming special needs students difficulties in learning English at elementary schools In Bengkulu city. This research method is descriptive qualitative. The research instrument is in the form of Question Lists which are based on Harmer in (Naibaho, 2019). The results of the study, of the 10 roles of the teacher according to Harmer in (Naibaho, 2019) almost all the roles of the teacher in overcoming the difficulties of learning English for special needs students in Bengkulu elementary school are applied. There are 10 teacher roles in teaching special needs students, namely (1) controller (2) organizer (3) assessor (4) prompter (5) participant (6) resource (7) observer (8) tutor (9) performer and (10) teaching aids. only one role was not implemented, namely the tutor by the teacher at SD Fatma Kenanga because the special needs students had been accompanied by a companion teacher or shadow teacher to assist in learning activities, the researchers suggested that the role of the teacher in teaching special needs students to be emphasized more because teaching special needs students required extra skills for the teaching process. For future researcher who are interested in conducting similar research, it is advisable to conduct research on large samples or research subjects and also at other levels of education Key words : Teachers Roles, Special Needs Students, Difficulties